The Routledge international companion to emotional and behavioural difficulties - Cole, Ted.; Daniels, Harry.; Visser, John, 1946- (Routledge handbooks, 2013)
"Responding to disruptive or troubled pupils with emotional and behavioural difficulties (EBD) remains a highly topical issue. The challenges these children present relate to wider issues of continuing political concern: the perceived declining discipline in schools; school and social exclusion; the limits to inclusion for children with special needs; increasing mental health difficulties in children; youth crime and parenting skills. This topical and exhaustively-researched Companion examines the difficulties of defining EBD, and the dangers of allocating this imprecise label to children. Bringing together the work of contributors from fifteen countries and across four continents, this book features the research of leading experts in the global field of EBD, who discuss and debate educators' key concerns by: - looking at the overlaps between EBD, ADHD and mental health difficulties; - outlining the types of appropriate schooling for children with EBD; - urging readers to look beyond pupils' challenging behaviour in order to understand and respond to the social, biological and psychological causation; - considering the key areas of assessment, whole-school and targeted approaches that help pupils with EBD in mainstream and in special settings; - outlining helpful work with families, the crucial contribution of effective multi-agency working and the importance of supporting and developing teachers who work with challenging pupils. Containing contrasting views on controversial topics, this Companion's approachable style makes it an essential reference book for academics, policy makers, practitioners, educators and students who are working towards a higher degree in education"--